Molecular dynamics study of rapid boiling of thin liquid water film on smooth copper surface under different wettability conditions. (February 2020) - Wu, Nini; Zeng, Liangcai; Fu, Ting; Wang, Zhaohui; Lu, Chang
Highlights: Effects of pure and mixed wettability on rapid boiling of water are studied. A microfluidic layer which only formed in hydrophilic zone is an important mechanism. Effects of attraction of water molecules on evaporation are studied. A mixed wettability surface enhances boiling heat transfer. Abstract: This work aims to present theory of heat transfer on rapid boiling for pure wettability surfaces and mixed wettability surfaces based on molecular simulation. The simulation results showed that the temperature of water increased obviously and the maximum evaporation rate of water reduced significantly with the increase of hydrophilic for pure wettability surfaces. Furthermore, a microfluidic layer which was formed on all cases except hydrophobic surface (surface 4) was conducive to critical heat flux (CHF) improvement. Meanwhile, the attraction of water molecules upon hydrophobic region was smaller than that on hydrophilic region which was conducive to boiling heat transfer coefficient (HTC) improvement. A mixed wettability surface enhances boiling heat transfer by regulating vapor spreading behaviors over the heating copper surface compared with pure wettability surfaces.